Effects of thickness, processing technique, and cooling rate protocol on the flexural strength of a bilayer ceramic system - Lima, Julia M. C. [UNESP]; Souza, Ana Carolina O. [UNESP]; Anami, Lilian C. [UNESP]; Bottino, Marco A. [UNESP]; Melo, Renata M. [UNESP]; Souza, Rodrigo O. A. (Elsevier B.V., 2013)
Objective. To determine whether the thickness, processing technique, and cooling protocol of veneer ceramic influence the flexural strength of a bilayer ceramic system.Materials and methods. Sixty-four bar-shaped specimens (20 mm x 4 mm x 1 mm) of yttria-stabilized tetragonal zirconia (Vita In-Ceram YZ, Vita) were fabricated (ISO 6872) and randomly divided into 8 groups (n = 8) according to the factors processing technique (P - PM9 and V - VM9), thickness (1 mm and 3 mm), and cooling protocol (S - slow and F - fast). The veneer ceramics were applied only over one side of the bar-shaped specimens. All specimens were mechanically cycled (2 x 10(6) cycles, 84 N, 3.4 Hz, in water), with the veneer ceramic under tension. Then, the specimens were tested in 4-point bending (1 mm/min, load 100 kgf, in water), also with the veneer ceramic under tension, and the maximum load was recorded at first sign of fracture. The flexural strength (sigma) was calculated, and the mode of failure was determined by stereomicroscopy (30x). The data (MPa) were analyzed statistically by 3-way ANOVA and Tukey's test (alpha = 0.05).Results. ANOVA revealed that the factor thickness (p = 0.0001) was statistically significant, unlike the factors processing technique (p = 0.6025) and cooling protocol (p = 0.4199). The predominant mode of failure was cracking.Significance. The thickness of the veneer ceramic has an influence on the mechanical strength of the bilayer ceramic system, regardless of processing technique and cooling protocol of the veneer ceramic. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Zirconia; All-ceramic; Cooling protocol; Flexural strength; Thickness